Design of β-hairpin peptides for modulation of cell adhesion by β-turn constraint - Satyanarayanajois, Seetharama D. (2012)
The CD2−CD58 interaction in immune regulation and disease pathology has provided new targets for developing potential immunosuppressive agents. In the present study, we report the introduction of constraints to generate β-hairpin structures from the strand sequences of CD2 protein. The β-hairpin structures were induced in the designed peptides by introducing Pro-Gly sequences in the peptides. Results from NMR and MD simulation indicated that the peptides exhibited β-turn structure at the X-Pro-Gly-Y sequence and formed the β-hairpin structure in solution. The ability of these peptides to inhibit cell adhesion was evaluated by two cell adhesion assays. Among the peptides studied (1−4) (P1−P4), peptides 2−4 were able to inhibit cell adhesion between Jurkat cells and SRBC nearly 50% at 180 μM, and 80% inhibition between Jurkat cells and Caco-2 cells was seen at 90 μM. Peptide 1 did not show significant inhibition activity compared to control.